MENGGALI NILAI-NILAI BUDAYA YANG TERKANDUNG PADA MOTIF TENUN IKAT DI SUKU ENDE LIO DESA MANULONDO - Susanti Sulaiman; Rodja Abdul Natsir; Moh. Fitri (Yayasan Literasi Sains Indonesia, 2023)
This study aims to find out what cultural values ​​are contained in the woven woven motifs and how to preserve the cultural values ​​contained in the woven woven motifs in the Ende Lio Tribe, Manulondo Village, Ndona District, Ende Regency. The method used in this research is descriptive qualitative. Data collection techniques using observation, interviews and documentation. Data analysis techniques use techniques to draw conclusions (verification). The results of the study show that in Ende Regency, the Ende Lio tribe in Manulondo Village has various forms of motifs. In the process of making motifs there are also only based on the imagination of the weavers and there are also motifs that have cultural values. motifs that have cultural values, namely the motifs jara mesa (own horse), guns sendetu (a group of elephants), rote rego (broken and broken love) and semba (men's scarves or the oversized shawls of the mosalaki ri'a bewa). These motifs have several values, namely Religious Values, Socio-Cultural Values, Economic Values, and Aesthetic Values. As for the efforts to preserve the woven fabric, namely the collaboration between the government and the local community to create an woven group called the Kapokale woven group. This is so that the younger generation maintains their ancestral cultural heritage so that it does not become extinct in the millennial era like now.